ANALISIS BIBLIOMETRIK: CADMIUM SULFIDE (CdS) SEBAGAI KATALIS MENGGUNAKAN VOSVIEWER - Sinta Susilo; Asep Bayu Dani Nandiyanto (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2023)
This study aims to examine the development of research on cadmium sulfide (CdS) as a catalyst with a bibliometric approach using computational mapping analysis using the VOSviewer application. To support research, a reference manager application (Publish or Perish) is used to obtain article data from the Google Scholar database. The keyword "Cadmium Sulfide as a Catalyst" is used to guide the search process for the title and abstract of the article. There were 999 articles considered relevant. Articles used as study material are articles indexed in Google Scholar for the last 10 years of study period (2013 to 2022). The results of the analysis of the development of the publication of cadmium sulfide as a catalyst in the last 10 years show quite frequent fluctuations. Research fluctuations occurred from 2013 – 2015 (61, 89, 67 publications per year, respectively). In 2016 – 2019 there was an increase in research (81, 91, 94, 117 publications per year, respectively). In 2020 – 2022 there will be research fluctuations (113, 155, 131 publications per year sequentially). VOSviewer was used to determine the relationship between the number of published articles on cadmium sulfide as a catalyst and problem areas. This review can serve as a starting point for research related to other materials